Do early life factors explain the educational differences in early labour market exit? A register-based cohort study - Emma Carlsson; Tomas Hemmingsson; Jonas Landberg; Bo Burström; Emelie Thern (BMC, 2023)
Abstract Background Socioeconomic inequalities in labour market participation are well established. However, we do not fully know what causes these inequalities. The present study aims to examine to what extent factors in childhood and late adolescence can explain educational differences in early labour market exit among older workers. Methods All men born in 1951-1953 who underwent conscription examination for the Swedish military in 1969-1973 (n = 145 551) were followed from 50 to 64 years of age regarding early labour market exit (disability pension, long-term sickness absence, long-term unemployment and early old-age retirement with and without income). Early life factors, such as cognitive ability, stress resilience, and parental socioeconomic position, were included. Cox proportional-hazards regressions were used to estimate the association between the level of education and each early labour market exit pathway, including adjustment for early life factors. Results The lowest educated men had a higher risk of exit through disability pension (HR: 2.72), long-term sickness absence (HR: 2.29), long-term unemployment (HR: 1.45), and early old-age retirement with (HR: 1.29) and without income (HR: 1.55) compared to the highest educated men. Factors from early life explained a large part of the educational differences in disability pension, long-term sickness absence and long-term unemployment but not for early old-age retirement. Important explanatory factors were cognitive ability and stress resilience, whilst cardiorespiratory fitness had negligible impact. Conclusions The association between education and early exit due to disability pension, long-term sickness absence and long-term unemployment was to a large part explained by factors from early life. However, this was not seen for early old-age retirement. These results indicate the importance of taking a life-course perspective when examining labour market participation in later working life.